Highly sensitive ferromagnetic resonance measurement systems for magnetic thin films - Chang, Han Yong. (2013)
We have designed and optimized a vector network analyzer ferromagnetic resonance measurement system that characterizes the spin dynamics and Gilbert damping parameters of thin ferromagnetic film sample. The complete tester consists of hardware instrumentation, software control for experimental process and data collection, as well as post-data analysis for parameter extraction. The success of the implementation has been validated using CoFeB40 thin magnetic films.